Optimizing Power Control and Link Availability Prediction in Software Defined Mobile Ad-hoc Networks - Satheesh Kumar, N; Sathyanarayana, N (International Journal of Computer Sciences and Engineering, 2018)
Routing offers a challenge in MANET because mobility of nodes will motivate frequent link breaks and therefore frequent modifications in topology due to mobility, leading to frequent route exchange. Accordingly, QoS provisioning for software application turns into a challenge. When a link break takes place, the route has to be repaired locally or a new route needs to be found. All through change in route discovery after link break, packets may be dropped. This results in unnecessary wastage of the scarce node resources along with battery energy. In this paper, a novel mechanism has been proposed to predict the duration of latest route availability. This approach pursuits to enhance the Quality of Service (QoS) by predicting a link failure earlier than its incidence and routing the packets via an alternate path, while nodes are moving dynamically in Mobile Ad-hoc network. Availability of route is determined by using availability of links among the devices which are making the route. To estimate path's future availability, the prediction is mandatory for those links. Availability of a link among nodes depends on the mobility of nodes, energy intake by the nodes, channel fading and shadowing etc. However, node mobility is major contributing issue for link failures. The proposed mechanism for predicting the link is used to estimate the active link availability to the neighbors. Primarily based on this data, when link failure is anticipated among two nodes, proactively an alternative path is building up earlier to link breaks. This reduces the packet drops (data) and hence the recovery time. With the proposed approach the nodes life time will be improved and performance of the network will be improved.